Industrial solid waste phosphogypsum composite material as well as preparation method and application thereof
By mixing industrial solid waste phosphogypsum with other materials and calcining at low temperature, industrial solid waste phosphogypsum composite materials are prepared, which solves the problems of difficult treatment of phosphogypsum and environmental pollution in the existing technology, and realizes its effective application in highway base materials.
Patent Information
- Application Number
- CN202411766231.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-12-04
AI Technical Summary
The existing technology cannot effectively utilize industrial solid waste phosphogypsum, which makes it impossible to directly apply to the preparation of highway base materials. In addition, traditional pretreatment processes have problems such as waste of water resources, high energy consumption and environmental pollution.
By mixing industrial solid waste phosphogypsum with cement, microsilicon powder, cinder and phenolic resin, and calcined at 120°C to 140°C for 1h to 1.5h, an industrial solid waste phosphogypsum composite material with high hardness, high strength and good durability was obtained.
It has achieved the conversion of industrial solid waste phosphogypsum into semi-water gypsum powder at a lower calcination temperature and shorter time, which reduces energy consumption, improves the mechanical properties of the material, and solves the problem of environmental pollution during the treatment of phosphogypsum.
Smart Images

Figure CN119569407A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of building materials, and particularly relates to an industrial solid waste phosphogypsum composite material and a preparation method and application thereof. Background Art
[0002] Phosphogypsum is a waste product produced when phosphoric acid is produced in the phosphate fertilizer industry. About 5 tons of waste residue are discharged for every ton of phosphoric acid produced. Due to the rapid development of the phosphorus chemical industry, the output of phosphogypsum waste has also increased rapidly. The main chemical component of phosphogypsum is CaSO4·2H2O, which is similar to natural gypsum. However, since phosphogypsum contains soluble phosphorus, fluorine, free acid and other impurities, random discharge will cause serious pollution to the environment. Therefore, the waste residue is piled up, which not only occupies land, but also has an impact on the ecological environment if phosphogypsum is stored for a long time.
[0003] When the prior art applies phosphogypsum to building materials, the phosphogypsum needs to be pretreated to remove impurities and reduce the pollution of phosphogypsum to the environment. The traditional pretreatment process of phosphogypsum includes: water washing, calcination and neutralization. The water washing method is to remove the soluble impurities in the phosphogypsum by water washing, such as soluble phosphate, fluorine and free phosphoric acid, but the ability of water washing to remove impurities is limited, so it is necessary to repeatedly wash the water, resulting in a waste of water resources; at the same time, a large amount of water needs to be evaporated after washing, and the treatment cost is high; in addition, the wastewater generated by washing is easy to cause water resource pollution problems, so it is difficult to promote and apply it in large quantities. The neutralization method is to use lime to neutralize the phosphogypsum, which requires a large amount of lime, generally 10wt% of lime is required to effectively reduce the soluble phosphorus content, and the price of lime is expensive, so the neutralization method seriously reduces the economic benefits of the enterprise.
[0004] The calcination process can convert phosphogypsum into semi-hydrated gypsum powder, which has less pollution to the environment during use and will not affect the setting time and strength of cement. However, the calcination needs to reach a temperature of 150℃~180℃ and last for 1h~2h. The process consumes a lot of energy and has limited output.
[0005] At present, the materials used in highway pavement base are mainly crushed stone, gravel and slag. The excessive mining and extraction of these materials have a great impact on the environment. Therefore, developing a new highway base material that meets environmental protection requirements and has a certain strength is the problem we need to solve.
[0006] However, due to the technical defects that phosphogypsum cannot be used directly and is difficult to process, the existing technology cannot directly apply phosphogypsum to prepare highway base materials. Summary of the invention
[0007] In view of the deficiencies of the above-mentioned prior art, the present invention provides an industrial solid waste phosphogypsum composite material and its preparation method and application. The present invention uses industrial solid waste phosphogypsum as raw material, mixes with cement, microsilica powder, coal slag, phenolic resin and water, then granulates, and then calcines at 120°C to 140°C for 1h to 1.5h to obtain an industrial solid waste phosphogypsum composite material. Compared with the prior art calcination process, the present invention can realize the conversion of industrial solid waste phosphogypsum into semi-hydrated gypsum powder at a lower calcination temperature and a shorter calcination time, and the industrial solid waste phosphogypsum composite material obtained by the method of the present invention has high hardness, high strength and good durability. While solving the environmental impact of existing highway pavement base materials and the technical defects of phosphogypsum being environmentally unfriendly, the obtained industrial solid waste phosphogypsum composite material can be applied in the highway base.
[0008] In order to solve the above technical problems, the present invention adopts the following technical solutions:
[0009] A method for preparing an industrial solid waste phosphogypsum composite material comprises the following steps:
[0010] Industrial solid waste phosphogypsum, cement, microsilica powder, coal slag, phenolic resin and water are mixed, granulated and dried to obtain a precursor; the industrial solid waste phosphogypsum is used as the main raw material, and cement, microsilica powder, coal slag and phenolic resin are used as modifiers to modify the industrial solid waste phosphogypsum; cement and microsilica powder are used as gelling agents, coal slag reduces the energy consumption of converting the industrial solid waste phosphogypsum into semi-hydrated gypsum powder, and phenolic resin improves the comprehensive performance of the industrial solid waste phosphogypsum composite material, and overcomes the influence of pores generated after coal slag combustion on the mechanical properties of the industrial solid waste phosphogypsum composite material; then when the industrial solid waste phosphogypsum is converted into semi-hydrated gypsum powder CaSO4·0.5H2O for application, an industrial solid waste phosphogypsum composite material with high hardness, high strength and good durability is obtained.
[0011] The precursor is heated at 120°C to 140°C for 1h to 1.5h to obtain an industrial solid waste phosphogypsum composite material. The calcination temperature of the prior art for converting industrial solid waste phosphogypsum into semi-hydrated gypsum powder is 150°C to 180°C. Since the present invention uses coal slag and industrial solid waste phosphogypsum to compound, the conversion of industrial solid waste phosphogypsum is achieved while reducing the calcination temperature; a temperature higher than 140°C will cause CaSO4·2H2O to be converted into anhydrous CaSO4, and a temperature lower than 120°C will result in incomplete calcination, causing pollution to the environment.
[0012] Preferably, the mass ratio of industrial solid waste phosphogypsum, cement, microsilica powder, phenolic resin and coal slag is 100:20~40:3~6:5~10:4~8, and the amount of phenolic resin is higher than the amount of coal slag, so as to improve the mechanical properties of the industrial solid waste phosphogypsum composite material by using phenolic resin.
[0013] Preferably, the particle sizes of coal slag and phenolic resin are both micron-sized. Coal slag and phenolic resin with micron-sized particles not only have the function of filling the voids in cement, but also produce a porous structure after the coal slag is burned, which is convenient for gas overflow and improves the conversion efficiency of industrial solid waste phosphogypsum. Further, the particle size of phenolic resin is less than 50 μm, the particle size of coal slag is 50 μm to 100 μm, and microsilica powder, phenolic resin and coal slag form a particle size gradient, which then achieves dense filling in cement and improves the strength of the industrial solid waste phosphogypsum composite material.
[0014] Preferably, the industrial solid waste phosphogypsum is a waste material generated when phosphoric acid is produced in the phosphate fertilizer industry, and its main chemical component is CaSO4·2H2O. The mass percentage of CaSO4·2H2O in the industrial solid waste phosphogypsum is 80% to 98%. The present invention processes CaSO4·2H2O with very high purity and can achieve efficient conversion of CaSO4·2H2O.
[0015] Preferably, the microsilica fume is selected from Aiken 940 microsilica fume, and the average particle size thereof is 0.1 μm to 0.15 μm. The microsilica fume not only fills the voids in cement, but also participates in cement hydration. Therefore, when the particle size is smaller, the cement and microsilica fume are mixed more evenly and form a dense structure, thereby improving the strength of the industrial solid waste phosphogypsum composite material after cement hydration.
[0016] The present invention also protects the industrial solid waste phosphogypsum composite material prepared by the preparation method.
[0017] Preferably, the particle size of the industrial solid waste phosphogypsum composite material is 5 mm to 20 mm. If the particle size is less than 5 mm, the particle size is too small to be used as a highway base material; if the particle size is greater than 20 mm, slippage is likely to occur between particles.
[0018] The present invention also protects the application of the industrial solid waste phosphogypsum composite material in the preparation of highway base materials.
[0019] Preferably, the application method is: using the industrial solid waste phosphogypsum composite material as filler to obtain a highway base material.
[0020] Preferably, the application method is: using industrial solid waste phosphogypsum composite material as aggregate, mixing and curing with concrete raw materials to obtain highway base material; the concrete raw materials include water reducer, water, and additives, and the additives include but are not limited to fly ash, silica fume, mineral powder, and kaolin.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] 1. The present invention uses industrial solid waste phosphogypsum, cement, microsilica powder, coal slag, phenolic resin and water as raw materials, and sequentially mixes and granulates to obtain a precursor, and then heats at 120°C to 140°C for 1h to 1.5h to obtain an industrial solid waste phosphogypsum composite material. In the precursor, industrial solid waste phosphogypsum is used as the main raw material, and cement, microsilica powder, coal slag and phenolic resin are used as modifiers. After the coal slag is compounded with the industrial solid waste phosphogypsum, the coal slag provides a combustion site during calcination, and then the temperature is rapidly increased to quickly realize the conversion of the industrial solid waste phosphogypsum into semi-hydrated gypsum powder. However, when the coal slag is burned, pores are formed with the release of gas, and the pores affect the mechanical properties of the industrial solid waste phosphogypsum composite material. Based on this, phenolic resin is also used for compounding. The phenolic resin undergoes a cross-linking and curing reaction at high temperature, and polymerization is carried out during the curing process. Chemical bonds are formed between the phenolic resin molecules, and then a three-dimensional network structure is formed. The formed three-dimensional network structure effectively overcomes the strength weakening problem caused by the pores.
[0023] In addition, the present invention also uses cement and microsilica powder to compound with industrial solid waste phosphogypsum to realize the application of the industrial solid waste phosphogypsum composite material in the highway base. During the granulation and drying process, the cement undergoes a hydration reaction, and the microsilica powder can participate in the hydration reaction of the cement to form a denser cement matrix, thereby improving the compressive strength and flexural strength of the industrial solid waste phosphogypsum composite material. In addition, since the fine particles of the microsilica powder can fill the gaps between the cement particles, the capillary pores of the industrial solid waste phosphogypsum composite material are reduced, and the overall strength is enhanced.
[0024] In summary, the present invention uses industrial solid waste phosphogypsum, cement, microsilica powder, coal slag, phenolic resin and water as raw materials, realizes the transformation of industrial solid waste phosphogypsum at a relatively low temperature, and at the same time takes the selection of raw materials into consideration and combines the reaction occurring at high temperature to obtain an industrial solid waste phosphogypsum composite material with high hardness, high strength and good durability, and uses it as a highway base material.
[0025] The industrial solid waste phosphogypsum composite material obtained by the preparation method of the present invention can directly replace the crushed stone, gravel and slag in the prior art, and be used as a highway pavement base material, thereby overcoming the problem of excessive mining and extraction of crushed stone, gravel and slag causing impact on the environment; in addition, in the industrial solid waste phosphogypsum composite material, the industrial solid waste phosphogypsum is converted into semi-hydrated gypsum powder CaSO4·0.5H2O, and the semi-hydrated gypsum powder has little pollution to the environment during use, thereby overcoming the problem of environmentally unfriendly use of phosphogypsum.
[0026] 2. The present invention is calcined at 120°C to 140°C to convert phosphogypsum into semi-hydrated gypsum powder. The dry semi-hydrated gypsum powder has strong hardening property and good compressive strength. After calcination, cement and semi-hydrated gypsum powder are compounded. The semi-hydrated gypsum powder can improve the strength and durability of cement, thereby improving the mechanical properties of the industrial solid waste phosphogypsum composite material, and at the same time realize the secondary application of industrial solid waste phosphogypsum.
[0027] 3. The present invention is calcined at 120°C to 140°C. At this time, the cement may undergo certain physical and chemical changes. However, the main components of cement are calcium silicate and calcium aluminate, which remain stable at a calcination temperature of 120°C to 140°C. Such physical and chemical changes usually do not lead to significant changes in the main chemical structure of the cement, and no major chemical reactions or structural changes occur, thereby ensuring the structural stability of the industrial solid waste phosphogypsum composite material.
[0028] 4. In the present invention, microsilica powder and coal slag are often regarded as industrial wastes, so while realizing the treatment of industrial solid waste phosphogypsum, the secondary utilization of industrial waste is realized, and the industrial solid waste phosphogypsum is transformed into a new material that can be used as a highway base material. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is a scanning electron microscope image of the industrial solid waste phosphogypsum composite material obtained in Example 1 of the present invention. DETAILED DESCRIPTION
[0030] The specific embodiments of the present invention are described in detail below, but it should be understood that the protection scope of the present invention is not limited by the specific embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work belong to the protection scope of the present invention. The experimental methods described in the embodiments of the present invention are conventional methods unless otherwise specified.
[0031] Compared with the prior art, the calcination temperature of industrial solid waste phosphogypsum in the prior art is 150℃~180℃, the calcination time is 1h~2h, the calcination process consumes a lot of energy, resulting in limited output. In the present invention, by compounding coal slag with industrial solid waste phosphogypsum, the calcination temperature is reduced to 120℃~140℃, and the calcination time is reduced to 1h~1.5h, that is, the preparation of semi-hydrated gypsum powder is achieved while reducing energy consumption.
[0032] The technical solution of the present invention is further studied by using embodiments below, and the specific research methods and results are as follows:
[0033] Example 1
[0034] A method for preparing an industrial solid waste phosphogypsum composite material comprises the following steps:
[0035] Industrial solid waste phosphogypsum, cement, microsilica powder, coal slag, phenolic resin and water are mixed, granulated and dried at room temperature to obtain a precursor.
[0036] Among them, the particle size of phenolic resin is 40 μm, the particle size of coal slag is 70 μm, and the mass ratio of industrial solid waste phosphogypsum, cement, microsilica powder, phenolic resin and coal slag is 100:30:5:8:6.
[0037] The precursor was heated at 140° C. for 1 h to obtain an industrial solid waste phosphogypsum composite material.
[0038] Example 2
[0039] A method for preparing an industrial solid waste phosphogypsum composite material comprises the following steps:
[0040] Industrial solid waste phosphogypsum, cement, microsilica powder, coal slag, phenolic resin and water are mixed, granulated and dried at room temperature to obtain a precursor.
[0041] Among them, the particle size of phenolic resin is 50 μm, the particle size of coal slag is 100 μm, and the mass ratio of industrial solid waste phosphogypsum, cement, microsilica powder, phenolic resin and coal slag is 100:40:6:10:8.
[0042] The precursor was heated at 130° C. for 1 h to obtain an industrial solid waste phosphogypsum composite material.
[0043] Example 3
[0044] A method for preparing an industrial solid waste phosphogypsum composite material comprises the following steps:
[0045] Industrial solid waste phosphogypsum, cement, microsilica powder, coal slag, phenolic resin and water are mixed, granulated and dried at room temperature to obtain a precursor.
[0046] Among them, the particle size of phenolic resin is 20 μm, the particle size of coal slag is 50 μm, and the mass ratio of industrial solid waste phosphogypsum, cement, microsilica powder, phenolic resin and coal slag is 100:20:3:5:4.
[0047] The precursor was heated at 120° C. for 1.5 h to obtain an industrial solid waste phosphogypsum composite material.
[0048] Comparative Example 1
[0049] The preparation method of the industrial solid waste phosphogypsum composite material is the same as the preparation steps of Example 1, except that no coal slag and phenolic resin are added, and comprises the following steps:
[0050] Industrial solid waste phosphogypsum, cement, microsilica powder and water are mixed, granulated and dried at room temperature to obtain a precursor.
[0051] Among them, the mass ratio of industrial solid waste phosphogypsum, cement and microsilica powder is 100:30:5.
[0052] The precursor was heated at 140° C. for 1 h to obtain an industrial solid waste phosphogypsum composite material.
[0053] At this time, since the calcination temperature does not reach the conversion temperature of the industrial solid waste phosphogypsum, the industrial solid waste phosphogypsum in the obtained industrial solid waste phosphogypsum composite material has high pollution, so it is not suitable for large-scale paving on the road.
[0054] Comparative Example 2
[0055] The preparation method of the industrial solid waste phosphogypsum composite material is the same as the preparation steps of Example 1, except that no phenolic resin is added, and comprises the following steps:
[0056] Industrial solid waste phosphogypsum, cement, microsilica powder, coal slag and water are mixed, granulated and dried at room temperature to obtain a precursor.
[0057] Among them, the particle size of phenolic resin is 40μm, the particle size of coal slag is 70μm, and the mass ratio of industrial solid waste phosphogypsum, cement, microsilica powder and coal slag is 100:30:5:6.
[0058] The precursor was heated at 140° C. for 1 h to obtain an industrial solid waste phosphogypsum composite material.
[0059] Examples 1 to 3 of the present invention all produce industrial solid waste phosphogypsum composite materials with high hardness, high strength and good durability. The industrial solid waste phosphogypsum composite material of Example 1 is used as an example for research, and is compared with Comparative Examples 1 to 2. The specific research methods and results are as follows:
[0060] According to GB / T50107-2013 Concrete Strength Test and Evaluation Standard and GB / T50082-2009 Ordinary Concrete Long-term Performance and Durability Test Method Standard, the performance of the industrial solid waste phosphogypsum composite materials of Example 1 and Comparative Examples 1 and 2 were tested. The test results are shown in Table 1:
[0061] Table 1 Performance test table of industrial solid waste phosphogypsum composite materials of Example 1 and Comparative Examples 1 to 2
[0062]
[0063] The results show that the mechanical properties of Example 1 are significantly better than those of Comparative Examples 1 and 2, and the apparent density shows that the density of the industrial solid waste phosphogypsum composite material of Example 1 is higher; the apparent density of Comparative Example 1 and Comparative Example 2 shows that the phenolic resin effectively improves the density of the industrial solid waste phosphogypsum composite material. Comparison of Comparative Examples 1 and 2 shows that after the combustion of coal slag, the density of the industrial solid waste phosphogypsum composite material decreases due to the generation of pores, thereby reducing both the apparent density and the mechanical properties.
[0064] According to "GB / T5484-2012 Gypsum Chemical Analysis Method", "JC / T2073 Determination Method of Phosphorus and Fluorine in Phosphogypsum" and "GB / T36141 Building Gypsum Phase Composition Analysis Method", the industrial solid waste phosphogypsum composite materials of Example 1 and Comparative Examples 1 to 2 were tested, and the test results are shown in Table 2:
[0065] Table 2 Component contents of industrial solid waste phosphogypsum composite materials of Example 1 and Comparative Examples 1 to 2
[0066] Phosphogypsum raw materials Example 1 Comparative Example 1 Comparative Example 2 <![CDATA[CaSO4·2H2O%]]> 90.63 2.18 72.15 2.05 <![CDATA[CaSO4·0.5H2O%]]> -- 87.21 15.38 88.03 <![CDATA[Water-soluble P2O5%]]> 0.75 0.024 0.53 0.021 Water Solubility F% 0.29 0.015 0.22 0.014
[0067] The results in Table 2 show that the content of CaSO4·2H2O in the phosphogypsum raw material is 90.63%. In Example 1 and Comparative Example 2, in which phosphogypsum is mixed with coal slag and then calcined, the CaSO4·2H2O is effectively reduced, while the CaSO4·0.5H2O is effectively increased, indicating that the decomposition of CaSO4·2H2O is basically completely achieved with the assistance of coal slag; however, since the raw material of Comparative Example 1 does not contain coal slag, the complete decomposition temperature is not reached when calcined at 140°C, and only partial decomposition is achieved.
[0068] Compared with the phosphogypsum raw material, the water-soluble P2O5 and water-soluble F in Example 1 and Comparative Example 2 are effectively reduced, that is, the impurity content is significantly reduced, overcoming the problem of environmental pollution caused by industrial solid waste phosphogypsum. While the partial decomposition of CaSO4·2H2O in Comparative Example 1 leads to incomplete combustion of soluble phosphorus and fluorine, resulting in still high contents of soluble phosphorus and fluorine.
[0069] The industrial solid waste phosphogypsum composite material of Example 1 was tested by scanning electron microscope. The results are as follows: Figure 1 As shown, through Figure 1 It can be seen that the industrial solid waste phosphogypsum composite material contains some pores, which are introduced after the combustion of coal slag. Except for the pores, the industrial solid waste phosphogypsum composite material has a dense overall structure. The dense effect is achieved on the one hand by using microsilica powder, coal slag and phenolic resin with different particle sizes as raw materials to fill the gaps between cement particles, and on the other hand by using phenolic resin as raw material, which forms a network structure after heating and achieves complete density with cement.
[0070] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalent technologies, the present invention is also intended to include these changes and variations. The above-described embodiments are only preferred embodiments for fully illustrating the present invention, and their protection scope is not limited thereto. Equivalent substitutions or changes made by those skilled in the art on the basis of the present invention are all within the protection scope of the present invention, and the protection scope of the present invention shall be subject to the claims.
Claims
1. A method for preparing an industrial solid waste phosphogypsum composite material, characterized in that: The steps include: Industrial solid waste phosphogypsum, cement, microsilica powder, coal slag, phenolic resin and water are mixed, granulated and dried to obtain a precursor; The precursor is heated at 120° C. to 140° C. for 1 h to 1.5 h to obtain an industrial solid waste phosphogypsum composite material.
2. The method for preparing an industrial solid waste phosphogypsum composite material according to claim 1, characterized in that: The mass ratio of industrial solid waste phosphogypsum, cement, microsilica powder, phenolic resin and coal slag is 100:20~40:3~6:5~10:4~8.
3. The method for preparing an industrial solid waste phosphogypsum composite material according to claim 1, characterized in that: The particle size of the phenolic resin is less than 50 μm, and the particle size of the coal slag is 50 μm to 100 μm.
4. The method for preparing an industrial solid waste phosphogypsum composite material according to claim 1, characterized in that: Industrial solid waste phosphogypsum is the waste generated when producing phosphoric acid in the phosphate fertilizer industry. Its main chemical component is CaSO4·2H2O. The mass percentage of CaSO4·2H2O in industrial solid waste phosphogypsum is 80% to 98%.
5. The method for preparing an industrial solid waste phosphogypsum composite material according to claim 1, characterized in that: The microsilica powder is selected from Elkem 940 microsilica powder, and its average particle size is 0.1μm to 0.15μm.
6. An industrial solid waste phosphogypsum composite material obtained by the preparation method according to any one of claims 1 to 5.
7. The industrial solid waste phosphogypsum composite material according to claim 6, characterized in that: The particle size of the industrial solid waste phosphogypsum composite material is 5mm to 20mm.
8. Use of the industrial solid waste phosphogypsum composite material according to claim 6 in the preparation of highway base materials.
9. The use according to claim 8, characterized in that: The application method is: using the industrial solid waste phosphogypsum composite material as filler to obtain a highway base material.
10. The use according to claim 8, characterized in that: The application method is: using industrial solid waste phosphogypsum composite material as aggregate, mixing and curing with concrete raw materials to obtain highway base material.
Citation Information
Patent Citations
Phosphogypsum composite material
CN101219881A
Process for preparing beta-hemihydrate gypsum through low-temperature calcination of phosphogypsum
CN108558250A
Multi-element solid waste recycled aggregate and preparation process thereof
CN113149586A
Artificial aggregate manufactured by usingphospho-gypsum
KR1020020096785A
METHOD OF PRODUCING ARTIFICIAL FLUORSPAR (CaF2) FROM PHOSPHORIC ACID PRODUCTION WASTES (PHOSPHOGYPSUM) FOR USE IN MAKING CEMENT
RU2604693C1